Formation processes of R&D consortia: which path to take? Where does it lead? - Doz, Yves L.; Olk, Paul M.; Ring, Peter Smith (Strategic Management Journal, 2000)
Research into network formation generally takes one of two approaches. Either it examines the outcomes of variations in the context and motives of the formation without examining the dynamics of the process, or it identifies the sequence of activities during the formation but does not examine variations within the formation. In this paper we complement both approaches by examining variations within the formation process and their consequences. We take an exploratory approach. Our analysis of survey data collected on the formation process of 53 R&D consortia reveals two distinct formation paths. The first involves emergent processes, developing from changes in the environment and a common interest and similar views among potential members. In the second, the process appears to be engineered—a triggering entity actively recruits potential members to join in the consortium. We conclude the paper with propositions on the importance of these formation types for the development of strategic networks. Copyright © 2000 John Wiley & Sons, Ltd.